Processing of semantic and grammatical gender in Spanish speakers with aphasia. Issue 8 (3rd August 2022) - Piazza, G.; Calabria, M.; Semenza, C.; Poletto, C.
ABSTRACT: Background: Previous studies have argued that there are two types of linguistic gender: grammatical gender, which is arbitrarily assigned to nouns, and semantic gender, which depends on the gender of the referent. Aim: We explore the hypothesis that these two types of gender entail distinct cognitive processes by investigating the performance of people with aphasia at the level of sentence processing. Methods and Procedure: Nine people with aphasia (seven with fluent aphasia) and a control group of thirteen age-matched healthy participants took part in a constrained completion choice task. The participants had to complete sentences in a way that made the last word gender congruent. The subjects of the sentences had either Semantic gender ( enfermera, nurse; indicating the gender of the referent), Grammatical gender ( silla, chair), or Opaque-Grammatical gender ( tomate, tomato). Results: People with aphasia performed more poorly in all gender conditions than healthy controls. They also were less accurate in both the Grammatical and Opaque-Grammatical conditions than in the Semantic gender condition. Conclusion: We propose that because semantic gender provides more salient information, it is processed faster than grammatical gender.